AN INSIGHT INTO THE DIFFERENCES OF PSYCHOLOGICAL DISPARATE MOTIVATIONS BETWEEN HACKERS AND CRACKERS - Syed Muzaffar Hussain (Polteknik Ilmu Pemasyarakatan, 2022)
This paper considers two different classes of computer hackers, with a special emphasis on disparate motivations of hacking. Hackers’ psychology widely discussed in the media is almost entirely unexplored by psychologists. In this study, hackers’ and crackers’ motivation is investigated, using the study of values scale. One hundred and fourteen participants completed our online research instrument. The study of values and demographic data were questioned. Participants were categorized as hackers and crackers through their responses on two items questioned in the demographic datasheet. Results indicated that hackers were found higher on the motivations of seeking knowledge, aesthetic sense, social interactions, and mysticism while crackers were found more motivated due to their economical and political interests. Findings suggested that hackers hack for the thrill of learning and gathering information to gain intelligence. Hackers hack to make society a better place to live. Compared to hackers, crackers are incapable of normal social interactions, and their hacking is based on the motivations of getting money and power.